Science and Faith in Dialogue - Eberlin, Marcos (Reformed Theology in Africa, 2022)
Science and Faith in Dialogue presents a cogent, compelling case for concordance between science and theism. The term theism refers, in this book, to the belief in God's existence. Within theology, the term theism is often used to convey a range of presuppositions about the nature and attributes of God. Based on scientific and natural theological perspectives, two pillars of natural theology are revisited: the Cosmological Argument and the Argument from Design. The book argues that modern science provides undeniable evidence and a scientific basis for these classical arguments to infer a rationally justifiable endorsement of theism as being concordant with reason and science - nature is seen as operating orderly on comprehensible, rational, consistent laws, in line with the conviction that God is Creator.